Genomic analysis of shiga toxin-containing Escherichia coli O157:H7 isolated from Argentinean cattle - Amadio, Ariel; Bono, James L.; Irazoqui, Jose Matias; Larzabal, Mariano; Marques Da Silva, Wanderson; Eberhardt, María Florencia; Riviere, Nahuel Agustin; Gally, David; Manning, Shannon D.; Cataldi, Angel Adrian (Plos, 2021)
Cattle are the main reservoir of Enterohemorrhagic Escherichia coli (EHEC), with O157:H7 the distinctive serotype. EHEC is the main causative agent of a severe systemic disease, Hemolytic Uremic Syndrome (HUS). Argentina has the highest pediatric HUS incidence worldwide with 12–14 cases per 100,000 children. Herein, we assessed the genomes of EHEC O157:H7 isolates recovered from cattle in the humid Pampas of Argentina. According to phylogenetic studies, EHEC O157 can be divided into clades. Clade 8 strains that were classified as hypervirulent. Most of the strains of this clade have a Shiga toxin stx2a-stx2c genotype. To better understand the molecular bases related to virulence, pathogenicity and evolution of EHEC O157:H7, we performed a comparative genomic analysis of these isolates through whole genome sequencing. The isolates classified as clade 8 (four strains) and clade 6 (four strains) contained 13 to 16 lambdoid prophages per genome, and the observed variability of prophages was analysed. An inter strain comparison show that while some prophages are highly related and can be grouped into families, other are unique. Prophages encoding for stx2a were highly diverse, while those encoding for stx2c were conserved. A cluster of genes exclusively found in clade 8 contained 13 genes that mostly encoded for DNA binding proteins. In the studied strains, polymorphisms in Q antiterminator, the Q-stx2A intergenic region and the O and P γ alleles of prophage replication proteins are associated with different levels of Stx2a production. As expected, all strains had the pO157 plasmid that was highly conserved, although one strain displayed a transposon interruption in the protease EspP gene. This genomic analysis may contribute to the understanding of the genetic basis of the hypervirulence of EHEC O157:H7 strains circulating in Argentine cattle. This work aligns with other studies of O157 strain variation in other populations that shows key differences in Stx2a-encoding prophages.